2006
DOI: 10.1063/1.2212534
|View full text |Cite
|
Sign up to set email alerts
|

Form birefringence of oxidized porous silicon

Abstract: A network of preferentially oriented pores is shown to induce anisotropy of linear and nonlinear optical properties of oxidized porous silicon ͑OPS͒ films. Although the x-ray diffraction indicates the presence of amorphous phase in OPS samples, the near-infrared and visible transmission measurements reveal a strong in-plane anisotropy exceeding that for the crystalline quartz. This anisotropy modifies dramatically polarization properties of the nonlinear optical properties resulting in a strong anisotropy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Indeed, form birefringence applications transcend the biological field, even being used to study the characteristics and properties of man-made devices (Beche and Gaviot, 2003;Hamza et al, 2004;O et al, 2004;Neale et al, 2005;Pang et al, 2005;Vasanthan, 2005;Golovan et al, 2006). Furthermore, Beche and Gaviot (2003), when defining form birefringence (''In optics, an anisotropy property on the permittivity tensor, called form birefringence.…”
Section: General Aspects Of the Birefringent Imagesmentioning
confidence: 99%
“…Indeed, form birefringence applications transcend the biological field, even being used to study the characteristics and properties of man-made devices (Beche and Gaviot, 2003;Hamza et al, 2004;O et al, 2004;Neale et al, 2005;Pang et al, 2005;Vasanthan, 2005;Golovan et al, 2006). Furthermore, Beche and Gaviot (2003), when defining form birefringence (''In optics, an anisotropy property on the permittivity tensor, called form birefringence.…”
Section: General Aspects Of the Birefringent Imagesmentioning
confidence: 99%
“…The orientation of pores formed in crystalline silicon result in a strong Δ F thereby enhancing the nonlinear-optical interactions (Golovan et al 2006). Other examples have been found in the search for form birefringence modeling for sensors in porous silicon fi lms (O et al 2004).…”
mentioning
confidence: 99%
“…Because even mechanical properties depend on molecular order, birefringence and infrared dichroism are used to measure such orientation (Vasanthan 2005). Studies that employed the principles of form birefringence in structural fabrication established the relation between nanostructure and properties of porous silicon and form birefringence (Bêche and Gaviot 2003, O et al 2004, Neale et al 2005, Vasanthan 2005, Golovan et al 2006, Tsai et al 2006. Verbiest et al (1998) demonstrated a strong enhancement of nonlinear optical properties through supramolecular chirality, determined by interaction of the electric fi eld of light waves with molecules in a medium of propagation, which results in optical phenomena such as birefringence.…”
mentioning
confidence: 99%
“…During the last few years birefringence caused by form‐anisotropy of 2D nanostructures has been studied intensively both experimentally and theoretically for different systems in a wide spectral range. Artificial birefringence has been reported for porous silicon 1, porous alumina 2, 3, oxidized porous silicon 4, and porous GaP 5 in the visible and near infrared spectral regions. Also an artificial birefringence of stacked hollow acrylic pipes in a triangular array 6 in the microwave region has been demonstrated.…”
Section: Introductionmentioning
confidence: 97%